The Influence of Work Motivation and Organizational Commitment on Job Satisfaction at the Department of Population and Civil Registration of Barito Kuala Regency - Wulan Wurnongo; Ahmad Alim Bachri (Journal of Islamic Economic Scholar, 2022)
This study aims to analyze the effect of work motivation and organizational commitment on job satisfaction at the Department of Population and Civil Registration, Barito Kuala Regency. This research is explanatory. This researcher uses a questionnaire with 70 employees of the Population and Civil Registration Office of Barito Kuala Regency as a sample, using a saturated sample technique. Measurement of variables using a Likert scale technique with a weight scale from 1 to 5. To determine the effect of the variables studied, namely Work Motivation and Organizational Commitment on Job Satisfaction, the Multiple Linear Regression analysis tool was used. The analysis results show that work motivation has a negative and significant effect on job satisfaction. This means that the higher the work motivation of an employee, the lower the level of job satisfaction. The organizational commitment has a positive and significant effect on job satisfaction, which means that the higher the organizational commitment in an employee, the higher the level of job satisfaction of employees at the Population and Civil Registration Office of Barito Kuala Regency.